Efektivitas Problem Based Learning Berbantuan Media Ular Tangga terhadap Kemampuan Pemecahan Masalah Ditinjau dari Minat Belajar Siswa - Dewi Mekarsari; Agus Setiawan; Choirudin Choirudin (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model assisted by snakes and ladders game media on students' mathematical problem-solving ability in terms of learning interest on circle topics. This research employed a quasi-experimental method with a 2×2 factorial design involving 46 eleventh-grade students of SMA Taruna Gajah Mada Metro, divided into experimental and control groups. Data were collected through a problem-solving ability test and a learning interest questionnaire. Data were analyzed using two-way ANOVA. The results showed that the learning model had a significant effect on problem-solving ability. Students taught using PBL assisted by snakes and ladders media achieved higher scores than those taught conventionally. Learning interest also had a significant effect. However, there was no significant interaction between the learning model and learning interest ). The R Square value of 0.690 indicates that 69% of the variance in problem-solving ability is explained by the learning model and learning interest. Thus, PBL assisted by snakes and ladders media effectively improves students' mathematical problem-solving ability.